(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article presents pedagogical and psychological conditions for the development of creative qualities of students in general education schools, researches focused on the development of creative qualities of students in geography classes, and opinions on the step-by-step implementation of the process of creativity formation.